Recolonization by Collembola of rehabilitated bauxite mines in Western Australia - Greenslade, P.; Majer, Jonathan (1993)
The collembolan faunas of 30 bauxite mines rehabilitated by a range of different methods between 1966 and 1977, and three forest plots were surveyed in the spring and summer of 1978-79 with the aim of studying the restoration of decomposer activity in degraded areas. The rehabilitation methods included seeding and planting with a variety of native or exotic plant species. Physical and botanical parameters of the plots were also measured. Sixty species of Collembola were collected from the rehabilitated areas; nine of the 28 species found in the forest plots were not present on the mined sites. Principal components analysis suggested that the species richness of the collembolan community in rehabilitated areas is positively correlated with plot age. A parametric correlation analysis using a number of collembolan community characteristics revealed that, among other factors, the development of a species rich collembolan fauna is positively correlated with plant species richness and diversity, and also with percentage plant cover. These results provide directions for improving rehabilitation practices.